Methodology of Organizing and Implementing Training Activities: Metodologi Pengorganisasian dan Implementasi Kegiatan Pelatihan - Ernazarov Alisher Ergashevich; Arifin Mado (Universitas Muhammadiyah Sidoarjo, 2024)
This study underscores the imperative of delineating a systematic approach to organizing training sessions within higher educational institutions, elucidating the requisite tasks integral to this process. It delves into the procedural intricacies and methodological nuances of implementing such training. The overarching goal is to enhance the efficacy of educational practices, emphasizing the need for a well-structured framework. Employing a rigorous analytical methodology, the study navigates through the planning, execution, and evaluation phases. The outcomes highlight the significance of clear objectives and flexible planning, illustrating the pivotal role of effective group dynamics and varied teaching methods. The study's implications extend to fostering discipline, motivation, and post-training support, ultimately contributing to the continuous development and application of acquired knowledge and skills. Highlights: Clear Objectives and Flexibility: Emphasizes the importance of precisely defined goals and objectives for training sessions while maintaining flexibility to adapt to the evolving needs of participants. Effective Group Dynamics: Highlights the role of establishing cohesive group dynamics during training sessions through activities fostering communication, cooperation, and trust among participants. Analytical Methodology: Utilizes a rigorous analytical approach to navigate through the planning, execution, and evaluation phases, ensuring a comprehensive understanding of the training process's intricacies. Keywords: Higher Education, Educational Process, Educational Training, Methodology, Educational Training Goal